MICROBIOLOGICAL QUALITY STUDIES OF GOAT MILK PANEER - Viji. K. S; K. Radha, K. Radha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Goat milk was incorporated at 25 per cent (T1), 50 per cent (T2) and 75 per cent (T3) levels with buffalo milk for the preparation of paneer. Paneer prepared from 100 per cent buffalo milk was used as control. Microbiological qualities of paneer at refrigerated as well as at room temperature storage were assessed. Statistical analysis revealed no significant difference between control and treatment paneer samples in total viable count, total coliform count and yeast and mould count. Freshly prepared paneer was creamy white in colour and had no goaty smell and salty taste. Coliforms and yeast and moulds were absent up to 5thday of refrigerated storage in all paneer samples.